Anticholinergic burden measures, symptoms, and fall-associated risk in older adults with polypharmacy: development and validation of a prognostic model - Dinh, Truc Sophia; Meid, Andreas; Rudolf, Henrik; Brückle, Maria-Sophie; González-González, Ana I.; Bencheva, Veronika; Gogolin, Matthias; Snell, Kym I. E.; Elders, Petra J. M.; Thürmann, Petra A.; Donner-Banzhoff, Norbert; Blom, Jeanet W.; et al. (PLOS ONE, 2023)
Anticholinergic burden has been associated with adverse outcomes such as falls. To date, no gold standard measure has been identified to assess anticholinergic burden, and no conclusion has been drawn on which of the different measure algorithms best predicts falls in older patients from general practice. This study compared the ability of five measures of anticholinergic burden to predict falls. To account for patients’ individual susceptibility to medications, the added predictive value of typical anticholinergic symptoms was further quantified in this context.
Gesehen am 13.12.2023